2004
DOI: 10.1051/lait:2004008
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between ruminant management and sensory characteristics of cheeses: a review

Abstract: -This review summarises the last 10 years' knowledge established on the relationships between the management of animals (genetics, physiology and feeding) and the sensory quality of cheese. In the production of full-fat raw milk cheese, the cow's breed can modify the texture of cheeses because of differences in fat in dry matter content due to variations in the fat/protein ratio in milk. Within the same breed, large differences in texture and taste were observed between cheeses issued from milk differing by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
120
2
12

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(141 citation statements)
references
References 76 publications
5
120
2
12
Order By: Relevance
“…The present results showed, in particular, that the LowGS treatment led to cheeses much more yellow than those produced with the HighMS treatment. This result, already observed in the case of cheeses produced in other regions of France (Verdier-Metz et al, 1998;Houssin et al, 2002;Coulon et al, 2004), is related to a larger intake of carotenoid-type pigments with a diet containing preserved grass (Noziè re et al, 2006). Calderon et al (2007), Coulon (1997), Hurtaud et al (2001), Noziè re et al (2006) and Verdier-Metz et al (2002) have shown that milks are more yellow when associated with grass silage diets.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The present results showed, in particular, that the LowGS treatment led to cheeses much more yellow than those produced with the HighMS treatment. This result, already observed in the case of cheeses produced in other regions of France (Verdier-Metz et al, 1998;Houssin et al, 2002;Coulon et al, 2004), is related to a larger intake of carotenoid-type pigments with a diet containing preserved grass (Noziè re et al, 2006). Calderon et al (2007), Coulon (1997), Hurtaud et al (2001), Noziè re et al (2006) and Verdier-Metz et al (2002) have shown that milks are more yellow when associated with grass silage diets.…”
Section: Discussionmentioning
confidence: 69%
“…On the other hand, breed did not affect the firmness of cheeses measured by penetrometry, even if No cows tended to produce cheeses slightly harder under the rind. Coulon et al (2004) reported that the differences between breeds would only be perceptible when the cheeses are made from fullcream milk (like the Pont-l'Evê que cheese in our trial).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Also, the pedoclimatic conditions dictate the botanical flora and, of course, the botanical composition of grass on which the living of these animals is based. In turn, the botanical composition of the pasture affects the organoleptic properties of the cheeses produced, especially their flavour, particularly when they are manufactured from raw milk [12].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies regarding the relationship between grass quality and milk have so far been done on bulk milk samples from very small tours (few herds) [6,12,31]. Therefore, it would be interesting to validate the relevance on representative milk samples.…”
Section: Introductionmentioning
confidence: 99%